2023
DOI: 10.1044/2023_jslhr-22-00506
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Context Can Mask Intelligibility Declines at Above-Conversational Speech Levels in Normal-Hearing Listeners

Abstract: Purpose: While speech audibility generally improves with increasing level, declines in intelligibility are inconsistently observed at above-conversational levels, even in listeners with normal audiograms (NAs). The inconsistent findings could be due to different types of speech materials, ranging from monosyllabic words to everyday sentences, used across studies. Here, we hypothesized that semantic context can “mask” intelligibility declines at high levels by constraining plausible response options… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…These authors argued that synaptopathy in LSR fibers may lead to a weaker middle-ear muscle reflex, which in turn can affect SI by reducing the attenuation of low-frequency input signals and thus increasing upward spread of masking. While Fereczkowski and Neher ( 2023b ) showed that RO can be found in listeners with normal audiograms when tested with highpass-filtered stimuli (i.e., under conditions of little, if any, upward spread of masking), the putative link between cochlear synaptopathy and speech perception (including RO) is likely both direct and indirect. More research is necessary to better understand its nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors argued that synaptopathy in LSR fibers may lead to a weaker middle-ear muscle reflex, which in turn can affect SI by reducing the attenuation of low-frequency input signals and thus increasing upward spread of masking. While Fereczkowski and Neher ( 2023b ) showed that RO can be found in listeners with normal audiograms when tested with highpass-filtered stimuli (i.e., under conditions of little, if any, upward spread of masking), the putative link between cochlear synaptopathy and speech perception (including RO) is likely both direct and indirect. More research is necessary to better understand its nature.…”
Section: Discussionmentioning
confidence: 99%
“…While monosyllabic words (and linear amplification) were used by Fereczkowski and Neher (2023a) , sentence-based materials were considered more suitable for evaluating the compression settings tested here. Further, since semantic context information can mask intelligibility declines at above-conversational presentation levels ( Fereczkowski & Neher, 2023b ), context-free sentences from the Danish DAT corpus ( Nielsen et al, 2014 ) were used for assessing SI in quiet. For assessing SI in noise, everyday sentences from the Danish version of the hearing-in-noise test (HINT; Nielsen & Dau, 2011 ) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Also, RO presence was associated with poorer speech-in-noise performance measured 10 dB above the individual most comfortable speech level, henceforth referred to as the 'MCL+10' level. In a subsequent study, we measured SI in quiet with nonlinear amplification [4]. A subset of the listeners from our previous study with clear RO was tested.…”
Section: Introductionmentioning
confidence: 99%